EVALUASI USABILITY FITUR SCREEN TIME BREAKS DAN SLEEP REMINDERS PADA TIKTOK UNTUK ETIKA KESEJAHTERAAN DIGITAL - Ziezou Claudi Putri Dewi; Evy Nurmiati (Jurnal Riset Sistem Informasi, 2026)
The rapid growth of social media, particularly TikTok, has raised significant concerns regarding addictive behavior and the digital wellbeing of its users. In response, TikTok has introduced "Screen Time Breaks" and "Sleep Reminders" features to assist users in managing their usage time. However, the effectiveness of these features heavily depends on their usability and ethical design transparency. This study aims to evaluate the usability of these two features using User Testing and the System Usability Scale (SUS) method, while analyzing them through the lens of digital wellbeing ethics. The testing was conducted on Information Systems students by measuring the Success Rate and Time on Task in locating and activating these features. The results of this study demonstrate the level of user ease in accessing time-management tools and whether TikTok's interface design supports or hinders the principles of Privacy by Design and Digital Wellbeing. These findings are expected to contribute to the development of application interfaces that are more humane and ethical in safeguarding user mental health. These findings emphasize the critical need for digital platforms to conduct periodic evaluations of their wellbeing features, ensuring that digital addiction intervention instruments are accessible, transparent, and accountably designed.